POLICY CHANGE – THE ROLE OF IDEAS AND POLICY ENTREPRENEURS - Arwanto, Arwanto; Anggraini, Wike (Fakultas Politik Pemerintahan, 2018)
ABSTRACT Understanding policy process involves many distinctive approaches. The most common are institutional, groups or networks, exogenous factors, rational actors, and idea-based approach. This paper discussed the idea-based approach to explain policy process, in this case policy change. It aims to analyse how ideas could assist people to understand policy change. What role do they play and why are they considered as fundamental element? It considers that ideas are belong to every policy actor, whether it is individual or institution. In order to answer these questions, this paper adopts Kingdon’s multi streams approach to analyse academic literatures. Through this approach, the relationship between ideas and policy change can be seen clearer. Ideas only can affect in policy change if it is agreed and accepted by policy makers. Therefore the receptivity of ideas plays significant role and it emerges policy entrepreneurs. They promote ideas (through problem framing, timing, and narrative construction) and manipulate in order to ensure the receptivity of ideas. Although policy entrepreneurs play significant role, political aspects remains the most important element in the policy process. Keywords: policy change, ideas, idea-based approach, Kingdon’s multiple streams, policy entrepreneurs.